Understanding Human Resource Management (HRM) - Jhonson Tri Syahputra Saragih; Herni Widiyah Nasrul; Oktavianti Oktavianti (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the level of understanding of Human Resource Management (HRM) and the factors that influence it in the context of modern organizations. HRM plays a strategic role in managing human potential to align with organizational goals, encompassing the functions of planning, recruitment, training, development, performance appraisal, and compensation. The research method used is quantitative with a descriptive approach. Data were collected through a structured questionnaire using a Likert scale to measure respondents' perceptions of the concept, function, and implementation of HRM. Data analysis was conducted using descriptive and inferential statistical techniques to describe the level of understanding and examine the relationship between variables. The results show that a good understanding of HRM is positively correlated with the effectiveness of employee management and increased organizational productivity. This finding emphasizes the importance of increasing literacy and continuous training in the field of HRM to support sustainable organizational performance. This study provides theoretical contributions to the development of the HRM concept and practical implications for organizations in improving human resource managerial competency.